Animal Pesticide Poisoning in Tunisia - Lahmar, Rym; Berny, Philippe; Mahjoub, Tarek; Ben Youssef, Samir (Frontiers in Veterinary Science, 2019)
During the period from 2014 to 2017, a retrospective study on pesticide poisoning in domestic animals and livestock was compiled and then analyzed. A total of 71 pesticide analyses have been submitted to the Pharmacy and Toxicology Laboratory of the School of Veterinary Medicine of Sidi Thabet in Tunisia. All the cases were first referred either through the clinical and/or pathological departments of the Veterinary School, the private and/or governmental veterinarians or directly by the pet owners. Among the total number of the suspected samples, 21 (29.6%) cases were found positive for various kinds of pesticides. Carbamate insecticides were the most frequently implicated pesticide (52.4% of the total positive cases), followed by organophosphate insecticides (19%), then rodenticides-anticoagulants and rodenticides non-anticoagulants (14.3% each). Therefore, carbamates and organophosphates are the most implicated group of pesticides in intoxications (71.4%). Among the 21 positive cases were 11 dogs, 4 cats, 3 poultry, 2 ruminants, and 1 case of bee poisoning. Partition chromatography (HPLC) has been used to characterize the incriminated pesticides. The aim of this survey was to determine incidence and characteristics of pesticide poisoning in domestic and farm animals in Tunisia. The reported results are useful for epidemiological cartography and medical management of intoxicated animals.